The Effect Of Mitragynine Addiction In Rats On Histone Regulations And Neuroplasticity - Suleiman, Yunusa (2024)
Mitragynine (MIT) was reported to develop addiction and impair cognitive functions. In acute studies, MIT was found to disrupt hippocampal synaptic transmission and distort memory via unknown mechanisms. This project evaluated the impact of 14 days of MIT exposure on the modulation of histone, synaptic transmission, and its potential mechanisms as well as dopaminergic, GABAergic, cholinergic, and glutamatergic systems in the rats’ brains. The impact of pharmacological inhibition of histone deacetylase enzyme on MIT action was also evaluated.